Studi Fenomenologi Penerapan Metode Pembelajaran Self Directed Learning Plus (SDL+) Pada Mahasiswa AKPER YKY Yogyakarta - Tenang Aristina; Dian Novita Kumalasari; Dwi Juwartini (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2025)
Medical and health education provides clinical skills training through skills laboratories, which are simulation programs in which medical students receive material and various methods and procedures related to different medical cases. Peer-assisted learning is a learning process in which designated or assigned students help their peers who experience learning difficulties. In the global era, nursing students are required to master knowledge, attitude, and clinical skills in various fields. This study aims to explore students’ experiences in the implementation of the Self-Directed Learning Plus (SDL+) method. The research design used in this study is qualitative research with a phenomenological approach, which involves describing, interpreting, and analyzing experiences in depth. Data analysis was conducted using the Colaizzi method. The results of the interviews indicate that the implementation of the SDL+ method among fourth-semester students at STIKES YKY Yogyakarta is less effective. Students reported experiencing difficulties and expressed limited understanding of the material delivered. This is because they are accustomed to conventional learning methods; therefore, when introduced to a new learning approach, they tend to struggle to adapt. Meanwhile, the main prerequisites for implementing SDL are student independence and initiative. Students’ experiences in the domain of cognitive skill improvement through the implementation of the SDL+ learning method show a non-significant increase in cognitive abilities in understanding lecture material. Additionally, students experienced difficulties when participating in lectures using the SDL+ method